GREEN HOTELS DEVELOPMENT POLICY AS A LOW CARBON TOURISM DEVELOPMENT EFFORT IN INDONESIA - christianto, Jery; Amalia, Affrida; Furqan, Alhilal (International Journal of Sustainable Competitiveness on Tourism, 2023)
This research analyzes the implementation of the green hotel development policy as a low-carbon tourism development effort in Indonesia during the era of President Joko Widodo's administration. This paper discusses what is meant by green hotel development, low carbon tourism development, and climate change risk management. This research is qualitative descriptive research that analyzes secondary data with a cross-sectional study design. The results of this study show that the Government of Indonesia has called for four strategic steps in dealing with climate change. Ensuring that all countries contribute to tackling climate change; mobilizing the potential of the community to raise awareness in dealing with and implementing actions related to climate change; Strengthening global partnerships by prioritizing capacity building cooperation in dealing with climate change for countries in the Pacific region; besides that, there are also four other efforts that have been carried out, namely the government targeting greenhouse gas reduction, the law on environmental protection and management, and the development plan national medium term, or RPJMN; establishing the management agency for environmental funds; national economic recovery; and food estate. Examples of hotels implementing green hotels in Indonesia are Borobudur Hotel Jakarta, Greenhost Boutique Hotel Yogyakarta, etc.